The Role of Regional Development Agencies in Turkey - Hüsnüoğlu, Nadide; Altınel, Ezgi (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
Regional development agencies can be characterised as semi-autonomous organisations that, in a multi functional and integrated manner, support economic development primarily through ‘soft’ means of policy, such as the provision of advice to SMEs inducing networking and learning. These agencies are implemented in EU and many other countries and leading organizations in development. Establishing regional development agencies in Turkey started with the effect of the process of joining EU. The main role that is imposed to these agencies are to guide the regional development and revive the regional economy. These agencies are in a position that is motivating development in these regions. In this study we excamined what roles RDAs are expected to play as part of the state’s organisational structure and policy programmes, versus a role as a self-sustaining strategic and/or operational agent and broker in particular regional settings. Whilst theories such as ‘new regionalism’ suggest that RDAs can lead integrated, bottom-up regional development actions, it is questionable whether Turkish RDAs have the capacity to adapt to the type of role that proponents of this approach expect.

Agencje rozwoju regionalnego mogą być scharakteryzowane jako półautonomiczne organizacje, które w sposób wielofunkcyjny i zintegrowany wspierają rozwój regionalny, głównie poprzez „miękkie” narzędzia polityki, takie jak porady dla MSP wspierające tworzenie sieci i uczenie się. Agencje te zostały utworzone w UE i wielu innych państwach oraz zalecane są przez organizacje działające na rzecz rozwoju. Powołanie agencji rozwoju regionalnego w Turcji rozpoczęło się w wyniku procesu integracji z UE. Główne zadanie, jakie zostało przypisane tym agencjom to wspieranie regionalnego rozwoju i stymulowanie gospodarki regionalnej. W opracowaniu skonfrontowano oczekiwaną rolę ARR jako części państwowych struktur organizacyjnych i realizacji programów politycznych z rolą samodzielnego strategicznego oraz operacyjnego agenta specyficznych regionalnych warunków. Podczas gdy teorie takie jak „nowy regionalizm” sugerują, że ARR mogą prowadzić do zintegrowanego, oddolnego rozwoju regionalnego, jest dyskusyjne, czy tureckie ARR mają zdolności do adaptacji do roli, jaką wyznaczają im zwolennicy tego podejścia.